Smoothelin-like protein 1 promotes insulin sensitivity and modulates the contractile properties of endometrial epithelial cells with insulin resistance - Keller, Ilka; Ungvári, Ádám; Kinter, Richárd; Szalmás, Fanni; Kókai, Endre; Lontay, Beáta (Frontiers in Endocrinology, 2024)
The incidence of infertility is significantly higher in women with diseases linked to impaired glucose homeostasis, such as insulin resistance. Defective glucose metabolism interferes with fertilization; however, the molecular mechanism underlying this interference is unclear.Smoothelin-like protein 1 (SMTNL1) was isolated from muscle and steroid hormone-responsive tissues and regulates the contractile functions of various cell types through the inhibition of myosin phosphatase (MP) holoenzyme. In addition, SMTNL-1 after phosphorylation at Ser301 by protein kinase A translocates to the nucleus and functions as a transcriptional co-activator of the progesterone receptor-B. SMTNL1 null mice exhibit reduced reproductive fitness and are more prone to type 2 diabetes mellitus. However, the role of SMTNL1 in endometrial epithelial cells is not known. We show that SMTNL1 promotes the differentiation of endometrial epithelial cells in a progesterone-dependent manner to attenuate insulin resistance. Furthermore, SMTNL1 hampers the migration capacity of epithelial cells in a gestational diabetes model by inhibiting the expression of MYPT1, the regulatory subunit of MP, and the activity of the holoenzyme, resulting in increased phosphorylation of the 20 kDa regulatory myosin light chain. SMTNL1 also acts as an insulin-sensitizing agent by increasing the gene expression of PP2A and DUPS9 protein phosphatases, resulting in decreased ERK1/2 activity and, hence, decreasing the phosphorylation of IRS-1 at Ser612 under gestational diabetes conditions. In conclusion, SMTNL1 may have therapeutic relevance to the progesterone-dependent inhibition of endometrial epithelial cell migration under hyperglycemic conditions and insulin sensitivity in the endometrium in gestational diabetes or other metabolic disorders.